How to Make Feedback More Effective? Qualitative Findings from Pilot Testing of an Audit and Feedback Report for Endoscopists. (18th September 2016) - Webster, Fiona; Patel, Jigisha; Rice, Kathleen; Baxter, Nancy; Paszat, Lawrence; Rabeneck, Linda; Tinmouth, Jill
Abstract : Background . Audit and feedback (A/F) reports are one of the few knowledge translation activities that can effect change in physician behavior. In this study, we pilot-tested an endoscopist A/F report to elicit opinions about the proposed report's usability, acceptability and usefulness, and implications for knowledge translation. Methods . Semi-structured qualitative interviews were conducted with eleven endoscopists in Ontario, Canada. We tested an A/F report template comprising 9 validated, accepted colonoscopy quality indicators populated with simulated data. Interview transcripts were coded using techniques such as constant comparison and themes were identified inductively over several team meetings. Results . Four interrelated themes were identified: (1) overall perceptions of the A/F report; (2) accountability and consequences for poor performance; (3) motivation to change/improve skills; and (4) training for performance enhancement and available resources. The A/F report was well received; however, participants cited some possible threats to the report's effectiveness including the perceived threat of loss of privileges or licensing and the potential for the data to be dismissed. Conclusions . Participants agreed that A/F has the potential to improve colonoscopy performance. However, in order to be effective in changing physician behavior, A/F must be thoughtfully implemented with attention to the potential concerns of its recipients.